The wide variation of amazonian stocked hardwoods affecting natural resistance to arboreal termites over time - de Sousa Silva, Ana Kelly; Castro Brasil Duarte, Marilia; Do Vale Gonçalves, Igor; Marcolino de Souza, Tiago; Tomazello, Mario; Livian Lima de Abreu, Juliana; Gomes da Silva, Marcela; Mendes, Lourival; Ferreira de Oliveira Neto, Cândido; Bufalino, Lina; de Paula Protásio , Thiago; Costa Ferreira, Gracialda (Maderas. Ciencia y Tecnología, 2024)
After forest suppression in mining areas, deterioration of stocked tropical hardwoods occurs at different rates and levels. Prioritizing logs to avoid wastage is challenging because the wide interspecific variability of wood traits makes natural resistance unpredictable. This work aimed to compare the biodeterioration of four Amazonian hardwoods from a mining stockyard to arboreal termite attacks over six weeks under laboratory conditions. The woods' chemical composition, anatomy, basic density, and crystallinity were determined. Mass loss and visual diagnosis of the specimens supported the biodegradability analyses. The species showed a wide range of mass loss after six weeks: Jacaranda copaia (pará-pará) - 15,2 %; Pseudopiptadenia suaveolens (timborana) - 0,8 %; Aegiphila integrifolia (tamanqueira) - 5,2 %; and Euxylophora paraensis (pau amarelo) - 0,5 %. Biodegradation did not stabilize over time for the lowest-density species. The crystallinity indicated the initial degradation of amorphous wood components, followed by a non-selective feeding mechanism. Gathering all species, increased extractive and lignin levels, fiber wall thickness, and basic density favored the natural wood resistance, oppositely to large vessel elements. The much lower basic density of J. copaia explains its lowest natural resistance. Wall thickness, pore diameter, and density overcame chemical composition on wood biodegradability. Low-density hardwoods stocked in mining yards are a priority for proper destinations.